Gap analysis of crop modeling activities within CGIAR and a community of practice (CoP) of 1,000 external members, with specific guidance on improved modeling practices. - CGIAR Platform for Big Data in Agriculture (2020)
Two reviews have been published containing the strengths, weaknesses and opportunities of crop modeling activities within the areas of Socio-economic and Breeding. Two more reviews will be submitted for publication during 2021 and a book chapter/white paper will be published that will also collect the CGIAR crop modeling gap analysis.